PENGARUH BRAND EXPERINCE DAN BRAND AFFECT TERHADAP KEPUASAN KONSUMEN PENGGUNA PRODUK APPLE DI KOTA DENPASAR - Rahayu, Diah Suci; Kusumadewi, Ni Made Wulandari (E-Jurnal Manajemen; Vol 2 No 11 (2013), 2013)
This study is about The Effect of  Brand Experience and Brand Affect To Customer Satisfaction of Apple Product Users in Denpasar. The aim of this study was to determine the effect of brand experience and brand affect to customer satisfaction of Apple product users in Denpasar simultaneously and partially and also to determine which variables are the dominant on influence customer satisfaction of Apple product users in Denpasar. This study used 100 respondents by purposive sampling technique. Data were analyzed by using multiple linear regression analysis. The results showed that in simultaneous and partia, brand experience and brand affect had significant effect on customer satisfaction of Apple product users in Denpasar and brand experience has dominant influence than brand affect. Through these results, it can be concluded that brand experience and brand affect influences consumer satisfaction of Apple product users in Denpasar. Keywords : brand experience, brand affect, customer satisfaction